The development of bali cattle reproductive research in Indonesia: Systematic literature review - Ardiansyah, M. F.; Prasetia, Muh. Andika; Aditama, Ryzal S.; Lena, Mirza; Sulfiar, Ahmat E. T. (Fakultas Peternakan Universitas Papua, 2025)
This study examines the development of Bali cattle farming in Indonesia using the Systematic Literature Review (SLR) method. The eastern region of Indonesia is recognized as a key center for cattle production, particularly Bali cattle, which demonstrate strong adaptability to suboptimal environmental conditions. Through the analysis of 555 scientific articles sourced from the Scopus database, this study identifies critical factors influencing farming success—namely, feed management, animal health, and husbandry systems. Although public interest in cattle fattening enterprises has increased, many farmers still rely on traditional practices without strategic planning. Visualization using the VosViewer application reveals dominant research themes, including reproductive performance, genetic diversity, and environmental stress factors. These findings underscore the urgency of multi-stakeholder collaboration to improve productivity, enhance competitiveness, and promote the genetic conservation of Bali cattle. The study provides valuable insights for advancing animal husbandry science and shaping more effective livestock development strategies.